TRIM6 affects the prognosis of acute myeloid leukemia through the PI3K/AKT signaling pathway and is associated with immune infiltration - Jingxin Zhang; Wu Zhou; Yuancheng Liu; Chenglong Hu; Siqi Wang; Jianxia Xu; Sixi Wei (PLoS ONE, 2025)
Objective Acute Myeloid Leukemia (AML) is a heterogeneous disease with limited therapeutic options and poor prognosis for patients. Therefore, the aim of this study was to evaluate the potential value of TRIM6 as a prognostic marker in AML. Methods In this study, the low-expressed gene TRIM6 was obtained by analysis of The Cancer Genome Atlas (TCGA-AML) and Genotype-Tissue Expression (GTEx) databases.The prognostic impact of TRIM6 was analyzed using Kaplan-Meier curves, univariate COX, multivariate COX, and columnar plot models. The signaling pathways associated with TRIM6 were obtained using Gene Set Variation Analysis (GSVA) and Gene Set Enrichment Analysis (GSEA) methods. Infiltrating immune cells associated with TRIM6 expression were analyzed using the “CIBERSORT” method. Mutations in AML patients were characterized using relevant Single Nucleotide Polymorphism (SNP) data. The effect of TRIM6 expression on AML cell progression was further analyzed by qRT-PCR, CCK-8 assay, flow cytometry and Western blot. Results By analyzing TCGA-AML and GTEx data, TRIM6 was found to be under-expressed in AML patients, and Kaplan-Meier curves, one-way and multifactorial Cox regression models suggested that under-expression of TRIM6 had a poor prognosis. In addition, monocyte, M2 macrophage and memory B cell infiltration levels were found to be higher in the TRIM6 low-expression group than in the TRIM6 high-expression group based on the “CIBERSORT” method. Further mutational characterization showed that TRIM6 expression was positively correlated with NPM1 mutations and negatively correlated with mutations in RUNX1, TP53 and ASXL1. Enrichment analysis revealed that TRIM6 expression was associated with the PI3K/AKT signaling pathway and immune response. In addition, in vivo and in vitro experiments further demonstrated that TRIM6 expression could inhibit AML progression via PI3K/AKT. Conclusion TRIM6 is expressed at low levels in AML, correlates with immune infiltration, and may affect AML progression through the PI3K/AKT signaling pathway.